Scenarios and state machines: models, algorithms, and tools a summary of the 4th workshop. - Bontemps, Yves (Software engineering notes.)
This report summarizes the Workshop on Scenarios and State Machines: Models, Algorithms, and Tools, held in St. Louis, Missouri, USA, on 21 May 2005, in conjunction with the International Conference on Software Engineering (ICSE 2005). The workshop consisted of a keynote and nine presentations. The workshop web page, which includes presented papers and the keynote presentation, can be found at http://www.info.fundp.ac.be/~ybo/scesm05/.